2020
DOI: 10.1093/mnras/staa631
|View full text |Cite
|
Sign up to set email alerts
|

The MAVERIC survey: a hidden pulsar and a black hole candidate in ATCA radio imaging of the globular cluster NGC 6397

Abstract: Using a 16.2 hr radio observation by the Australia Telescope Compact Array (ATCA) and archival Chandra data, we found > 5σ radio counterparts to 4 known and 3 new X-ray sources within the half-light radius (r h ) of the Galactic globular cluster NGC 6397. The previously suggested millisecond pulsar (MSP) candidate, U18, is a steep-spectrum (S ν ∝ ν α ; α = −2.0 +0.4 −0.5 ) radio source with a 5.5 GHz flux density of 54.7 ± 4.3 µJy. We argue that U18 is most likely a "hidden" MSP that is continuously hidden by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 147 publications
1
24
0
Order By: Relevance
“…A mag- gravitational potential well, and thus a neutron star or black hole accretor. Alternatively, "redback" millisecond pulsars (with nondegenerate, mass-losing companions of >0.1 𝑀 ) can also match all the data; several candidate redbacks have recently been identified in other globular clusters without the detection of radio pulsations (Zhao et al 2020a;Urquhart et al 2020). Our ATCA radio observations allow a (3𝜎) 5 GHz radio luminosity limit of 1.1 × 10 27 erg s −1 , which along with the 1-10 keV 𝐿 𝑋 of 8.7 × 10 31 erg s −1 , are not deep enough to rule out a black hole (e.g.…”
Section: Cx5mentioning
confidence: 87%
“…A mag- gravitational potential well, and thus a neutron star or black hole accretor. Alternatively, "redback" millisecond pulsars (with nondegenerate, mass-losing companions of >0.1 𝑀 ) can also match all the data; several candidate redbacks have recently been identified in other globular clusters without the detection of radio pulsations (Zhao et al 2020a;Urquhart et al 2020). Our ATCA radio observations allow a (3𝜎) 5 GHz radio luminosity limit of 1.1 × 10 27 erg s −1 , which along with the 1-10 keV 𝐿 𝑋 of 8.7 × 10 31 erg s −1 , are not deep enough to rule out a black hole (e.g.…”
Section: Cx5mentioning
confidence: 87%
“…For instance, Bogdanov et al (2010) suggested an X-ray source in the cluster NGC 6397 (source ID U18 in their work) as a strong MSP candidate, given its similar X-ray and optical properties to those of the known MSP, PSR J1740−5340, in the cluster. Later, Zhao et al (2020a) found the radio counterpart to U18 using the Australia Telescope Compact Array, while Pichardo Marcano et al ( 2021) reported the optical modulation of the companion star to U18, and both of their studies provided strong evidence that U18 is a "hidden" redback MSP. The radio pulsations from this source have been detected recently by the Parkes radio telescope (Lei Zhang et al 2021, in prep.…”
Section: Discussionmentioning
confidence: 99%
“…), verifying it as a redback MSP (PSR J1740−5340B). The reason of previous non-detection of radio pul- sations can be interpreted as scattering of the radio pulsations by wind from the companion (Zhao et al 2020a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observationally, there are a growing number of BH candidates that have been identified in Galactic and extragalactic GCs (Maccarone et al 2007;Strader et al 2012;Chomiuk et al 2013;Miller-Jones et al 2015;Bahramian et al 2017;Shishkovsky et al 2018;Giesers et al 2018Giesers et al , 2019Zhao et al 2020). Some clusters, such as M 22 (Strader et al 2012) and NGC 3201 (Giesers et al 2018(Giesers et al , 2019, are found to host more than one BH candidate, strongly supporting the existence of a BHS in these systems.…”
Section: Introductionmentioning
confidence: 95%